Features of morphological and functional characteristics and physical preparedness of sprinters 15-16 years old, specializing in various swimming methods - Elena Politko; Liliya Sheyko (Kharkiv State Academy of Physical Culture, 2020)
Purpose: to develop model morphological and functional characteristics and indicators of physical preparedness of 15-16-year-old sprint swimmers specializing in various swimming methods. Material & Methods: analysis and generalization of scientific and methodological literature, pedagogical observation, testing, anthropometric measurements, methods of mathematical statistics. Results: scientific knowledge on the features of the morphological and functional characteristics and physical preparedness of sprint swimmers specializing in various methods of swimming is supplemented. The study of the level of physical fitness showed a difference in the development of motor qualities of sprinters depending on their main way of swimming, which is due to the structure of the technique of performing movements in water. Conclusions: the results allow us to say that the objectivity of sports orientation in sprinting depends on the integrated use of morphological, functional and pedagogical criteria, which can make it possible to establish the tendency of young athletes to this or that way of swimming.